Financial literacy, financial management practices, and retirement confidence among women working in government agencies: a mediation model - Sabri, Mohamad Fazli; Teo, Tze Juen; Othman, Mohd Amim; Abdul Rahim @ Abdul Wahab, Husniyah (Australian Academy of Business and Social Sciences, 2015)
Concerns regarding the retirement experience of pre-retirees are growing globally. Numerous discussions on factors affecting retirement confidence can be found in academia. The present study employed structural equation modelling in the attempt to examine the mediating role of financial management practices on the relation between financial literacy and retirement confidence. A mediation model was tested on a sample of 626 Malaysian women working in government agencies. Significant relations were found between financial literacy, financial management practices, and retirement confidence. Earlier analysis revealed that the relation between financial literacy and retirement confidence is spurious, as the relation is fully mediated by financial management practices. The result supports the Family Resource Management Theory introduced by Deacon and Firebaugh (1988). Implications of the findings and suggestions for future studies are offered.